Wangjiao Kamen / [videorecording (DVD)] - Wong, Kar-wai, 1958-; Lau, Andy, 1961-; Zhang, Xueyou; Zhang, Manyu; Wan, Ziliang; Deng, Guangrong, 1946- (Kino International Corp., 2004)
"Already stretched to breaking in a loyalty tug of war between Triad bosses and his loose cannon partner, Wah, a rising star in the HK underworld, finds himself saddled with beautiful, ailing country cousin Ngor. As an escalating test of wills with a stubborn debtor explodes into bloodshed and a mob turncoat instigates a ruthless police crackdown, Wah's growing fascination with Ngor becomes his last chance for escape from a violent past and a dubious future." -- Container.